Transgenic T-cell receptor immunotherapy for cancer: building on clinical success - Natasha Oppermans; Gray Kueberuwa; Robert E. Hawkins; John S. Bridgeman (SAGE Publishing, 2020)
With the advent of immunotherapy as a realistic and promising option for cancer treatment, adoptive cellular therapies are gaining significant interest in the clinic. Whilst the recent successes of chimeric antigen receptor T-cell therapies for haematological malignancies are widely known, they have yet to show great success in solid cancers. However, immune cells transduced with T-cell receptors have been shown to traffic to and exert anti-cancer effects on solid tumour cells with some great successes. In this review, we explore the field of transgenic T-cell receptor immunotherapy, highlighting some of the key clinical trials which have paved the way for this type of cellular immunotherapy. Some trials have shown amazing clinical results, including long-term remissions and minimal toxicity, and can be looked at as an exemplar for this adoptive cell therapy. There have also been key trials where unexpected, fatal, off-tumour toxicity has occurred, and these trials have also been instrumental in shaping safer clinical trials, particularly regarding preclinical testing. In addition to previous trials, we analysed the current clinical trial space for T-cell receptor T-cell therapy, showing which trials are dominating in the clinic and which targets are being prioritised by researchers around the world. By looking at both past and current trials, we have been able to identify key drivers in developing transgenic T-cell receptor immunotherapy for the future.